Hubungan Kepatuhan Minum Obat Terhadap Kadar Gula Darah Sewaktu Pada Penderita Diabetes Mellitus Tipe 2 - Made Rismawan; Ni Made Tisna Handayani; I G.A. Rai Rahayuni (Jurnal Riset Media Keperawatan, 2023)
Diabetes mellitus is a group of metabolic diseases or disorders characterized by hyperglycemia that occurs due to abnormalities in urine secretion, insulin action or both. The level of patient compliance in taking medication is one of the factors that determine the success of diabetes mellitus therapy. Patients who adhere to taking medication have normal blood sugar levels and patients who do not adhere to taking medication have high blood sugar levels. Purpose: This study aims to determine the relationship of medication adherence to blood sugar levels during type 2 diabetes mellitus. Method: The design of this research is descriptive correlational with a cross sectional approach. The sample used in this study were 57 people who were taken using a non-probability sampling technique with a consecutive sampling approach. Data collection used a questionnaire on the level of compliance from the theory of the Morisky Medication Adherence Scale (MMAS-8) and the results of blood sugar levels during the examination. Furthermore, the data were analyzed using the Spearman Rho test. Results: Most people with diabetes mellitus taking medication were in the high category, which was 47.4%, and their blood sugar levels were mostly in the normal range, which was 63.2%). The results of the bivariate analysis found that there was a significant relationship between adherence to taking medication and blood sugar levels during type 2 diabetes mellitus (p value = 0.000) with the strength of the relationship in the moderate category (r = 0.492). Conclusion: Patient compliance is necessary to achieve successful diabetes mellitus therapy so that it indirectly plays a role in stabilizing blood glucose levels in diabetes mellitus patients.